Um estudo sobre o momentum angular total de estrelas com planetas - Santana, Juliana Cerqueira de (2011)
Since Michel Mayor and his student Didier Queloz s pioneer announcement, in 1995, of the existence of a planet orbiting the star 51 Peg, up to present date, 695 extrasolar planets orbiting stars of spectral type F, G, K and M have been discovered. A study on the behavior of the total angular momentum of the planetary systems known up to present date becomes relevant when we know that about 98% of the angular momentum of the solar system is associated with the planets, although they represent only 0.15 percent of the mass of the whole system. In this dissertation we study the behavior of stellar angular momentum, orbital angular momentum and total angular momentum in a sample of 282 stars harboring planets, including 40 multiple systems. We observed that planetary systems containing more than one known planet have both higher orbital angular momentum and total angular momentum compared to those who have only one planet. This analysis shows that multiplanet systems tend to have higher momenta, suggesting that the planets in such systems that contribute to the greater portion momenta have been found. Thus, planetary systems with lower values for the momenta represent the best candidates to the discovery of new planets